Styrene-carbon dioxide phase equilibria at high pressures - Akgün, M; Emel, D; Baran, N; Akgün, NA; Deniz, S; Dinçer, S (ELSEVIER, 2004)
High pressure vapor-liquid equilibrium data for the binary system styrene and carbon dioxide were measured using the static method. Experiments were carried out at temperatures and pressures between 333.15 and 348.15 K, and 6 and 13 MPa, respectively. Experimental results were correlated with the Peng-Robinson equation of state using conventional mixing rules with one interaction parameter. (C) 2003 Elsevier B.V. All rights reserved.
Keywords: vapor-liquid equilibria; equation of state; high pressure; styrene; carbon dioxide; SIZE POLYSTYRENE PARTICLES; BEHAVIOR; POLYMERIZATIONS; SYSTEM; Chemistry; Engineering